ANALISIS PENERAPAN ECONOMIC ORDER QUANTITY (EOQ) DI PABRIK GULA MADUKISMO BANTUL - Risa Rahmawati; Endang Siti Rahayu; Susi Wuri Ani (Caraka Tani: Journal of Sustainable Agriculture, 2017)
The purpose of this research to analyze the result of Economic Order Quantity in Madukismo Sugar Manufacture during the year of 2013-2015. The basic method used in this research was analytical, descriptive with case study technique. Data analysis used Economic Order Quantity (EOQ). The results of the study showed that during 2013-2015 the order quantity according to Madukismo Sugar Manufacture policy was 29.377 Quintal with the frequency of ordering 192 times, 30.328.46 Quintal with the frequency of ordering 168 times, and 31.883,06 Quintal with the frequency of ordering 142 times, sequentially. Whereas the result of Economic Order Quantity (EOQ) calculation during 2013-2015 where 52,916.47 Quintal with the frequency of ordering 107 times, 45,980.57 Quintal with a frequency 111 times, and 49,135.20 Quintal with a frequency 92 times, consecutively. The result of Economic Order Quantity calculation to intent filled up the needs of sugar cane and to maintain the sustainability of the production process. The effort to provide Economic Order Quantity of sugarcane,Madukismo Sugar Manufacture managed for expanding of sugarcane planting area. So that, Madukismo Sugar Manufacture could run the production process properly and sustainability.